Cytotoxic T lymphocytes and viral adaptation in HIV infection. - Goulder, P; Klenerman, P (2006)
PURPOSE OF REVIEW: Cytotoxic T lymphocytes are central in determining the extent of immune control of HIV infection. We examine the degree to which one may trace the steps that underlie these human leucocyte antigen/disease outcome associations. These findings will be of relevance to HIV vaccine design. RECENT FINDINGS: Initial investigations suggested that immune escape was inevitably associated with loss of control of viral replication. Recent studies of successful immune control of HIV infection, however, indicate that immune selection pressure on the virus may in certain circumstances result in viral adaptation with a reduced replication capacity. The dominant influence of particular human leucocyte antigen B alleles on HIV disease outcome is echoed in hepatitis C infection, and major histocompatibility complex class I alleles in the non-human primate that are associated with control of simian immunodeficiency virus infection also share similar mechanisms of viral control. SUMMARY: Cytotoxic T lymphocyte-mediated selection pressure on HIV has important consequences for subsequent immune control within the host. The extent to which viral adaptation occurs in the general population to alter these consequences is complex and epitope-specific, but is critical to the ongoing effectiveness of particular cytotoxic T lymphocyte responses through the course of the epidemic.